EVALUASI KINERJA PEMASOK DENGAN METODE ANALYTICHIERARCHY PROCESS - Saktiva Moryza Zahir (Universitas Mercu Buana, 2014)
Abstract. This study aims to determine the performance assessment criteria forsuppliers with better criteria based on previous research and the study ofliterature, also measure the performance of suppliers using the criteria. Theresearch data is the data performance per supplier during the period January toAugust 2013. The sampling method used is a saturated sampling where the entirepopulation is taken as a sample with a population of 9 people and 3 people for asample of experts. The analytical method used in this study is the AnalyticalHierarchy Process (AHP). The results showed that the criteria can be used in thecompany and of the simulation shown significant results from suppliers that serveas sample simulations. The criteria are include quality and durability testing,delivery, price, responsiveness, financial stability and business, informationdevelopment process, technical ability and a good & stable background. Afterdone supplier performance assessment using criteria that already selectedresulting effective measurement, example using 3 company supplier which isgenerating a decision for best supplier selection that can cooperate with companypositively. Assessment can be done for improving supplier performance withpurpose improving performance based on worse criteria that supplier has.Keywords: Supplier Performance Assessment, AHP, Analytical HierarchyProcess, Supplier Performance Effective Measurement, Supplier Selection &Decision